Investigation of process parameters on flexural properties for CFRP composites. (2023) - Tanna, Jilesh; Kagathara, Raj; Shah, Dhaval B.; Joshi, Shashikant; Bhojawala, Vipul
Highlights: The CFRP laminates have been fabricated according to ASTM D790 to measure flexure properties using the wet layup compression method. The flexural strength and flexural modulus have been obtained experimentally and numerically using ABAQUS. With an increase in the thickness of the specimen, the flexural strength increases nonlinear manner. There is no significant influence of change in thickness on the flexural modulus. The unidirectional laminate with [0]5S stacking sequence shows a higher flexural strength and flexural modulus than cross-ply laminates with [0, 90, 0, 90, 0] and [45, 0, 90, 45, 0] stacking sequences. The results of the present work would be helpful to designers and composite manufacturers in selecting the proper thickness and stacking sequence according to application. Abstract: Advanced materials like composites are being increasingly used nowadays because of their excellent mechanical properties. Carbon fiber reinforced polymers (CFRP) are one such type of advanced composites that offer high strength to weight ratio, high modulus, high flexural strength, and very low coefficient of thermal expansion. The flexural properties are important mechanical characteristics for any advanced material. In this research paper, the effect of process parameters on the flexural behaviour of the CFRP sheet has been investigated experimentally and numerically. The thickness of laminate and ply stacking sequence or ply orientation have been considered as process parameters. The CFRP laminates have been fabricated using the wet layup compression method. The samples have been prepared according to ASTM D790 to measure flexure properties. The flexural strength and flexural modulus have been obtained for different laminate thicknesses with various stacking sequences. The finite element (FE) simulation has been performed for the same process parameters using ABAQUS. The assembly of the test setup has been modelled followed by assigning proper material properties and applying boundary conditions for simulation. The results from experimental and simulation techniques have been compared and it has been found that flexural strength increases with an increase in laminate thickness while there is no significant influence of thickness on flexural modulus. It has also been observed that flexural properties change dramatically for different ply-stacking sequences. The results of the present work would be helpful to designers and composite manufacturers in selecting the proper thickness and stacking sequence according to application.